PENGEMBANGAN WISATA DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN BREBES - Medi Tri Purwanto (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2020)
AbstrakThe tourism development in Brebes Regency is more inclined to the development of natural tourism areas such as the Ranto canyon waterfall, the princess waterfall, Kaliwlingi mangrove forest and the Pany Host waterfall. The development is carried out in an effort to improve the quality of these tourist attractions. Where, the development carried out by the local government is to improve the infrastructure in tourist areas, such as repairing good roads. This is done because the tourism is an asset owned by the regency of Brebes Regency.